Defect-induced optical and electrochemical properties of Pr2Sn2O7 nanoparticles enhanced by Bi3+ doping. Issue 9 (14th May 2020) - Abraham, Allen; Gupta, Santosh K.; Mohan, Swati; Abdou, Hisham; Mao, Yuanbing
Abstract: Abstract : Materials that show superior light-emitting and catalytic properties are in high demand among the scientific community owing to their applications in the areas of optoelectronics and (opto)electrocatalysis. In this work, we have synthesized sub-10-nm Pr2 Sn2 O7 (PSO) and Pr2 Sn2 O7 :Bi 3+ (PSOB) nanoparticles (NPs) and investigated their optical and electrochemical properties. On ultraviolet irradiation, PSO NPs display blue emission because of the presence of oxygen vacancies. Interestingly, PSOB NPs have higher blue emission intensity than undoped PSO NPs owing to the increase in oxygen vacancy defect density induced by Bi 3+ doping. Moreover, PSOB NPs display higher efficiency in terms of current density than PSO NPs as a catalyst toward the oxygen evolution reaction (OER). The kinetic OER models of PSO and PSOB NPs are quite different as displayed by their different Tafel slopes. Interestingly and as another advantage, the PSOB sample is more conducting with low impedance value than the PSO counterpart. With all these advantages due to high oxygen vacancies induced by Bi 3+ doping, PSOB NPs have a great potential to be used as blue phosphors, charge storage devices, and capacitors.